Renovation of sewage risers - Kolonko, Andrzej (Instal, 2023)
In the paper the problem of sewage riser renovation is discussed as an alternative to traditional replacement procedure associated with demolition works that are burdensome for the inhabitants of buildings. The relatively short history of application of non-demolition methods in sewage riser renovation is presented, which was initiated after 2000 in Finland.